Ciri Visual Bentuk Arsitektur Masjid Lama Gang Bengkok dalam Akulturasi Budaya - Naibaho, Polin DR; Yulianto, Yulianto; Pakpahan, Raimundus (Unika Santo Thomas, 2024)
Medan City has a variety of ethnicities and cultures that cannot be separated from its past (history). The city of Medan, which is now known as